The Islamic perspective on outbreaks - Ahmed Shogar, Ibrahim Adam (2021)
For outbreak of any new viral disease, three things are need to be determined: Naming the disease, Type of the virus, and Name of the species. The World Health Organization (WHO) is responsible for the first task (common name of the virus or the disease), the virologists are responsible for the second, and the International Committee on Taxonomy of Viruses (ICTV) is concerned with the designation and naming of virus taxa (i.e. species, genus, family, etc.)